2017
DOI: 10.1103/physrevb.95.180302
|View full text |Cite
|
Sign up to set email alerts
|

Critical behavior at dynamical phase transition in the generalized Bose-Anderson model

Abstract: Critical properties of the dynamical phase transition in the quenched generalized Bose-Anderson impurity model are studied in the mean-field limit of an infinite number of channels. The transition separates the evolution towards ground state and towards the branch of stable excited states. We perform numerically exact simulations of a close vicinity of the critical quench amplitude. The relaxation constant describing the asymptotic evolution towards ground state, as well as asymptotic frequency of persistent p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Contrary to conversional classical (quantum) phase transitions driven by temperature (magnetic field or pressure), DQPTs are considered as new types of phase transitions driven by time. There has been a lot of interest in the study of DQPTs, including critical properties [4][5][6][7][8][9][10][11] , dynamical order parameters [12][13][14][15] , and spontaneously broken symmetries [16][17][18][19][20][21] , etc. The realizations of DQPTs have been performed in a large number of experiments based on different platforms [22][23][24][25][26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to conversional classical (quantum) phase transitions driven by temperature (magnetic field or pressure), DQPTs are considered as new types of phase transitions driven by time. There has been a lot of interest in the study of DQPTs, including critical properties [4][5][6][7][8][9][10][11] , dynamical order parameters [12][13][14][15] , and spontaneously broken symmetries [16][17][18][19][20][21] , etc. The realizations of DQPTs have been performed in a large number of experiments based on different platforms [22][23][24][25][26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it has been recently shown that real-time evolution of time-independent many-body systems after a quantum quench, i.e. a sudden change of a control parameter of systems, across a critical value can reveal non-analytical behavior at certain moments of time [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The critical behavior in time evolution has been also observed for quenches within the same phase [35,36].…”
Section: Introductionmentioning
confidence: 99%